Factors affecting site supervision in improving IBS productivity - Wan Ramizah, Wan Salleh (2019)
Successful delivery of construction of IBS projects needs an effective supervisor’s that have a combination of strong technical, interpersonal, communication and managerial skills. Unfortunately, a consistent finding is that there are many factors that affecting site supervision and most construction works are not delivered on time and consequently have a problem during installation of IBS. Therefore, the main aim of the study is to identify the factors affecting site supervision in improving IBS productivity. The study adopts a questionnaire survey approach to elicit information from the respondents, and out of the seventy questionnaires administered fifty-five were retrieved. The information and the data from the questionnaires were analyzed using average index method. The study will focused on factors affecting site supervision and problem during installation of IBS. Therefore, the ways to enhance site supervision in improving IBS productivity will be produced in this study. From the finding analysis, the main factors affecting site supervision is on-site construction process. While the main problem during installation of IBS is required planning on time delivery. It is recommended that the quality of IBS product or components should be enhanced to promote better site supervision.